A model of field induced stripe texture in the cholesterics with extremely short pitch. Issue 8 (21st June 2019) - Lejček, Lubor; Novotná, Vladimíra; Glogarová, Milada
ABSTRACT: We deal with undulation-like deformations in cholesteric liquid crystalline compounds with short pitch. The short-pitch cholesterics behave as a layered smectic A liquid crystal and for molecules with the positive dielectric anisotropy the applied electric field leads to reorientation of the long molecular axis to the field direction. When the field energy is comparable to the anchoring energy above a threshold value necessary for creation of 'cholesteric layer' undulations, the 'cholesteric layers' at surfaces start to be tilted and arrays of cylindrical domains near both surfaces are induced. Cylindrical domains can be described by ( ± π)-disclination pairs. In this contribution, the disclination model is developed to explain the stripe texture observed in previously studied cholesterics under a sufficiently high electric field. The model also allows us to estimate the surface anchoring energy. Graphical Abstract: